'It's personal to me': A qualitative study of depression in young people with CFS/ME. (April 2017) - Taylor, Anna K; Loades, Maria; Brigden, Amberly LC; Collin, Simon M; Crawley, Esther
Background: Paediatric chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) has a prevalence of 0.4–2.4% and is defined as 'generalised disabling fatigue persisting after routine tests and investigations have failed to identify an obvious underlying cause'. One-third of young people with CFS/ME have probable depression. Little is known about why depression develops, the relationship between depression and CFS/ME, or what treatment might be helpful. Methods: We conducted nine semi-structured interviews with young people with CFS/ME (aged 13–17 years, 8/9 female) and probable depression, covering perceived causes of depression, the relationship between CFS/ME and depression, and treatment strategies. Results: Most thought CFS/ME caused depression. Many discussed a cyclical relationship: low mood made CFS/ME worse. A sense of loss was common. CFS/ME restricted activities participants valued and changed systemic structures, causing depression. There was no single helpful treatment approach. Individualised approaches using combinations of cognitive behavioural therapy (CBT), medication, activity management and other strategies were described. Conclusion: This study suggests that depression may be secondary to CFS/ME in young people because of the impact of CFS/ME on quality of life. Clinicians treating young people with CFS/ME need to consider strategies to prevent development of depression, and research is needed into approaches that are effective in treating CFS/ME with co-morbid depression.